Behaviorism Theory in a Language Environment: A Case Study of Arabic Language Proficiency at Pesantren Al-Bukhari, Southeast Sulawesi: Teori Behaviorisme dalam Lingkungan Berbahasa: Studi Kasus Penguasaan Bahasa Arab di Pesantren Al-Bukhari Sulawesi Tenggara - Khofifah Khofifah; Agung Setiyawan; Mujahid Al Ghifari; Achmad Khairul Umam (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2025)
Abstract Purpose – This study aims to analyze the application of behaviorism theory in the language environment and its impact on Arabic language proficiency among santri at Pesantren Al-Bukhari Wesalo. The research focuses on two main questions: (1) how behaviorism theory is implemented, and (2) what factors influence the effectiveness of this environment in enhancing students’ mastery of the Arabic language. Design/methods/approach – A descriptive qualitative approach with a case study design was used. Participants included santri and language program coordinators. Data were collected through participatory observation, semi-structured interviews, and documentation. Data validity was ensured through source and technique triangulation. Analysis followed Miles and Huberman's model: data reduction, display, and conclusion drawing. Findings – The findings indicate that Skinner’s behaviorist principles are implemented through various language programs, including daily Arabic conversations, vocabulary memorization, thematic speeches, and summarizing Arabic media. Reinforcement is applied through punishments or fines for rule violations. Internal factors such as motivation, self-confidence, and aspirations to study in the Middle East, along with external factors like the school environment, social interactions, and teacher support, contribute to the program's effectiveness. Research implications/limitations – While the implementation is generally effective, challenges remain in student participation and limited learning facilities. This study is also limited in scope to a single pesantren (Islamic boarding school) and does not yet include the integration of digital technology. The study does not yet address the integration of digital technology. Originality/value – This study confirms that behaviorism theory can effectively enhance Arabic language proficiency through reinforcement and habituation. It also highlights opportunities for integrating digital technology in similar educational contexts. Furthermore, the study opens opportunities for integrating behaviorism with digital technology in other educational institutions. Abstrak Tujuan – Penelitian ini bertujuan untuk menganalisis penerapan teori behaviorisme dalam lingkungan berbahasa dan dampaknya terhadap penguasaan bahasa Arab santri di Pondok Pesantren Al-Bukhari Wesalo. Fokus penelitian ini mencakup dua hal: (1) bagaimana teori behaviorisme diterapkan dalam lingkungan berbahasa di pesantren, dan (2) faktor-faktor apa saja yang memengaruhi efektivitasnya. Desain/metodologi/pendekatan – Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Subjek terdiri atas santri dan koordinator program bahasa di pesantren. Data dikumpulkan melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi. Keabsahan data diperoleh melalui triangulasi sumber dan teknik. Analisis data mengikuti model Miles dan Huberman: reduksi data, penyajian, dan penarikan kesimpulan. Temuan – Hasil penelitian menunjukkan bahwa prinsip behaviorisme Skinner diterapkan melalui berbagai program kebahasaan, seperti penggunaan bahasa Arab dalam percakapan sehari-hari, hafalan mufrodat, pidato tematik, serta kegiatan menonton dan merangkum media Arab. Penguatan berupa hukuman atau denda diberikan kepada santri yang melanggar aturan berbahasa. Faktor internal seperti motivasi, kepercayaan diri, dan aspirasi studi ke Timur Tengah, serta faktor eksternal seperti lingkungan pesantren, interaksi sosial, dan dukungan guru, berkontribusi terhadap efektivitas program. Implikasi/Batasan Penelitian – Meskipun implementasi program telah berjalan baik, masih terdapat tantangan berupa partisipasi santri yang belum maksimal dan keterbatasan sarana pembelajaran. Studi ini juga terbatas pada ruang lingkup satu pesantren dan belum mencakup integrasi teknologi digital. Orisinalitas/Nilai – Penelitian ini menegaskan bahwa penerapan teori behaviorisme efektif dalam meningkatkan penguasaan bahasa Arab melalui pembiasaan dan penguatan. Studi ini juga membuka peluang untuk mengembangkan pendekatan serupa dengan integrasi teknologi digital di lembaga pendidikan lainnya.